Impact of experimental pressure and temperature on semiclathrate hydrate formation for pre-combustion capture of CO2 using tetra-n-butyl ammonium nitrate - Babu, Ponnivalavan; Datta, Stuti; Kumar, Rajnish; Linga, Praveen (Energy, 2014)
TBANO(3) (tetra-n-butyl ammonium nitrate) is a promising liquid phase promoter for capturing CO2 via HBGS (hydrate based gas separation) technology. In this study, the impact of experimental pressure and temperature on formation of mixed CO2-H-2-TBANO(3) semiclathrate hydrate for the optimum 1.0 mol% TBANO(3) reported by Babu et al. [1] was investigated. Experimental pressures of 3.0, 4.5 and 6.0 MPa and temperatures of 274.2, 276.2 and 278.2 K were employed. Irrespective of the experimental pressure, shorter induction time was observed for experiments conducted at 274.2 K when compared to the experiments at other temperatures. At a given pressure, the total gas uptake increased with increase in experimental temperature. Similarly at a given temperature, the total gas uptake increases with an increase in pressure. Higher rate of hydrate formation was observed at experimental pressure of 6.0 MPa than at 3.0 and 4.5 MPa irrespective of the experimental temperature. The CO2 composition in hydrate was between 87.5 and 93.2 mol%. Finally, the gas consumption for 1.0 mol% TBANO(3) as promoter was much higher than other promoters of quaternary salts like tetra-n-butyl ammonium bromide and tetra-n-butyl ammonium fluoride at comparable concentration and driving force. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: Carbon dioxide capture; Clathrate process; Gas hydrates; Semi-clathrates

Impact of pressure and temperature on tetra-n-butyl ammonium bromide semi-clathrate process for carbon dioxide capture - Babu, Ponnivalavan; Chin, Weng Inn; Kumar, Rajnish; Linga, Praveen (International Conference on Applied Energy, ICAE2014, 2014)
The pre-combustion capture of CO2 in an IGCC power plant employing the hydrate based gas separation (HBGS) process is a novel method currently receiving attention around the world. Tetra-n-butyl ammonium bromide (TBAB) is a promoter that has been shown to improve the efficiency of hydrate formation. In this study, the effect of temperature and pressure on 0.3 mol% TBAB solution is investigated. The induction time for the experiments conducted at 6.0 MPa and 274.8 K was found to be lower, while nucleation became increasingly random as temperature is increased and pressure is reduced. Total gas uptake and normalized rate of hydrate formation (NR5) is also the highest for the experiments conducted at 6.0 MPa and 274.8 K. However, it was found that the hydrate phase CO2 composition remains relatively constant at both reduced temperatures and pressures. (C) 2014 The Authors. Published by Elsevier Ltd.
Keywords: Carbon dioxide capture; Clathrate process; Gas hydrates; Gas separation; Promoters; tetra-n-butyl ammonium bromide